Double decoupling effectiveness of water consumption and wastewater discharge in China’s textile industry based on water footprint theory - Li, Yi (PeerJ, 2019)
As a traditional pillar industry in China, the textile industry has been intensifying the pressure of the water resource load and its reduction of water environment emissions over the years. Decoupling water resource consumption and wastewater discharge require decoupling from economic growth to realise the sustainable development of the textile industry. On the basis of water footprint and decoupling theories, this paper analysed the water consumption decoupling, wastewater discharge decoupling, as well as the double decoupling of water consumption and wastewater discharge of China’s textile industry and its three sub-industries (Manufacture of Textile, Manufacture of Textile Wearing and Apparel, Manufacture of Chemistry) from 2001 to 2015. In those years, the sum of the decoupling index in the double-decoupling years is 249, lower than that in high-decoupling years of water consumption (250) and wastewater discharge (325). Compared with the decoupling of water consumption and of wastewater discharge, the double decoupling is lower, which proves that the conditions for realizing double decoupling are stricter. The double decoupling analysis of water consumption and wastewater discharge, namely, the overall consideration of water resource consumption and water environment pollution, could be used to more effectively promote the realisation of water decoupling in the textile industry.